Keteladanan Guru dan Implikasinya terhadap Kecerdasan Emosional Siswa SDIT Teuku Umar Meulaboh Kabupaten Aceh Barat - Ruslan ND (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
Teachers are educators who can become role models for students and their environment. Teachers’ exemplary attitudes in educating are part of powerful and effective methods in preparing and shaping the moral, spiritual, and social aspects of the students. Teachers are an ideal example in the view of their students, with their behavior and manners often imitated. Whether the students realize it or not, all of these exemplary behaviors will be instilled within themselves and their feelings and manifested both in words and actions. This study used a qualitative approach. The data came from primary and secondary sources, collected through observation and interview. The subjects in this study included male and female students, homeroom teachers, and school principals at SDIT (integrated Islamic elementary school) Teuku Umar Meulaboh, West Aceh District. The results of the study showed that: 1) The actualization of role modeling carried out by the teachers at the SDIT included courtesy, greetings, interpersonal acts, discipline, handshaking, and establishing rapport with the students; 2) The obstacles in developing the emotional intelligence of the students at the SDIT consisted of bad influences from non-educational entertainment, family, and friends as well as environment. The solutions for these included collaboration of teachers and parents, in which both the school and the parents were open to receiving input/opinions; and 3) The implication of teachers’ role-modeling in learning on the emotional intelligence of the students at the SDIT is that the teachers as role models motivate the students to learn and behave well so that the students can have a capital for developing exemplary daily behaviors.